Validation of a Virtual Reality Buffet environment to assess food selection processes among emerging adults. (1st October 2020) - Cheah, Charissa S.L.; Barman, Salih; Vu, Kathy T.T.; Jung, Sarah E.; Mandalapu, Varun; Masterson, Travis D.; Zuber, Ryan J.; Boot, Lee; Gong, Jiaqi
Abstract: Emerging adulthood is a critical developmental period for examining food- and eating-related behaviors as long-term weight-related behavioral patterns are established. Virtual reality (VR) technology is a promising tool for basic and applied research on eating and food-related processes. Thus, the present study tested the validity and user perceptions of a highly immersive and realistic VR food buffet by: (1) comparing participants' food selections made in the VR buffet and a real-world (RW) food buffet cafeteria one-week apart, and (2) assessing participants' rated perceptions of their VR experience (0–100 scale). Participants comprised an ethnically diverse sample of emerging adults ( N = 35, M age = 20.49, SD = 2.17). Results revealed that participants' food selections in the VR and RW food buffets were significantly and positively correlated in Kcals, grams, carbohydrates, and protein (all p 's < 0.05). Moreover, participants perceived that: (a) the VR buffet was natural ( M = 70.97, SD = 20.92), (b) their lunch selection in the VR buffet represented a lunch they would select on an average day ( M = 84.11, SD = 15.92); and (c) their selection represented a lunch they would select if the same foods were available ( M = 91.29, SD = 11.00). Our findings demonstrated the validity and acceptability of our highly immersive and realistic VR buffet for assessing food selection that is generalizable to RW food settings one-week apart without precisely matched foods. The findings of this study support the utility of VR as a validated tool for research on psychological and behavioral food-related processes and training interventions among emerging adults.